A Nationwide Assessment of the Association of Smoking Bans and Cigarette Taxes With Hospitalizations for Acute Myocardial Infarction, Heart Failure, and Pneumonia. (December 2017) - Ho, Vivian; Ross, Joseph S.; Steiner, Claudia A.; Mandawat, Aditya; Short, Marah; Ku-Goto, Meei-Hsiang; Krumholz, Harlan M.
Multiple studies claim that public place smoking bans are associated with reductions in smoking-related hospitalization rates. No national study using complete hospitalization counts by area that accounts for contemporaneous controls including state cigarette taxes has been conducted. We examine the association between county-level smoking-related hospitalization rates and comprehensive smoking bans in 28 states from 2001 to 2008. Differences-in-differences analysis measures changes in hospitalization rates before versus after introducing bans in bars, restaurants, and workplaces, controlling for cigarette taxes, adjusting for local health and provider characteristics. Smoking bans were not associated with acute myocardial infarction or heart failure hospitalizations, but lowered pneumonia hospitalization rates for persons ages 60 to 74 years. Higher cigarette taxes were associated with lower heart failure hospitalizations for all ages and fewer pneumonia hospitalizations for adults aged 60 to 74. Previous studies may have overestimated the relation between smoking bans and hospitalizations and underestimated the effects of cigarette taxes.